Analisis Penggunaan Fluxion portable Untuk Menguji Wi-Fi dengan Keamanan WPA/WPA2 - Aziz, Aulia Syarif; Selian, Reja Anggara (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2025)
With the convenience offered by Wi-Fi networks, cybercrimes targeting Wi-Fi passwords have become increasingly prevalent. This study aims to evaluate the effectiveness of using fluxion portable as a tool for testing the security of WPA/WPA2-protected Wi-Fi networks. The research was conducted on a ZTE-F609 router using an action research approach to gain deeper insights into the method’s effectiveness. Fluxion portable operates by leveraging social engineering techniques, wherein attackers create a rogue access point that mimics the legitimate network. Through this social engineering method, unsuspecting users may enter their passwords on the rogue network. The findings indicate that fluxion portable is indeed effective in obtaining Wi-Fi passwords via psychological manipulation, which often goes unnoticed by users. These results highlight significant risks faced by Wi-Fi users, especially in environments lacking additional protections. To mitigate the potential threat of fluxion portable attacks, users are advised to hide their Wi-Fi network from public view or to use routers with enhanced security features, such as whitelist options. These recommendations are expected to improve Wi-Fi security and raise user awareness of existing potential threats.